X-ray phase contrast imaging of additive manufactured structures using a laser wakefield accelerator. (9th April 2019) - Vargas, M; Schumaker, W; He, Z-H; Behm, K; Chvykov, V; Hou, B; Krushelnick, K; Maksimchuk, A; Nees, J A; Yanovsky, V; Zhao, Z; Thomas, A G R
Abstract: X-rays generated by the betatron oscillations of electrons in a nonlinear plasma wakefield have been proposed to be useful for a range of applications. In this study, the scaling of the x-ray fluence and energy with electron beam properties and laser power are studied and the application of the x-rays for imaging additive manufactured (3D printed) test objects is investigated. The scalings confirm a strong increase in x-ray fluence with laser power and the imaging shows strong fringe contrast due to the micron scale source size.